TANGGUNG JAWAB PT. PRATAMA MAKMUR JAYA MEDAN TERHADAP BARANG BAWAAN MILIK PENUMPANG DALAM BAGASI BUS MAKMUR - Yerikho Alexandre; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The transport is a transfer of location, both to things and to people, an activity that guarantees passengers on the bus.Prior agreements would need to be established with passenger tickets or transport papers. With tickets to prove the agreement, customers and customers must fulfill their rights and obligations according to the 1999 statute no. 8 on consumer protection. PT. Pratama Makmur Jaya medan was one of the otobus companies. In progress, PT. Pratama Makmur Jaya on transporting both persons and cargo items and passenger packages by attabounding clausen on the condition of the transport agreement that was on the bus ticket to be jointly agreed upon. In practice, passengers have suffered losses caused by the negligence of both the transporters and the passengers themselves. To limit the duty of the transport vessel to make clause on the condition of the transport agreement on their bus ticket that reads "small things and nonfares are privately cared for and if lost" the result of this thesis is how the carrier handles the luggage of the passengers in the baggage of the Makmur bus, Does clausen "take care of small items and things that have no fares themselves and if missing becomes a load of their own owners" in bus tickets limiting the responsibilities of the transporters. The result of this study suggest that PT. Pratama Makmur Jaya Medan Has the responsibility of liability to compensate passengers for any damages inflicted by PT. Pratama Makmur Jaya Medan fault or negligence, if such negligence is proven then the person responsible for the loss is the employee. However, there are liability restrictions on the corresponding clausen ticket in PT. Pratama Makmur Jaya Medan And there is no responsible for the loss of passengers if it contradicts clausen in the transport agreemenKeywords : The laws of transportation, Transports, Passengers, Restitution